Artificial consciousness: the missing ingredient for ethical AI? - Chella, Antonio (Frontiers in Robotics and AI, 2023)
Can we conceive machines that can formulate autonomous intentions and make conscious decisions? If so, how would this ability affect their ethical behavior? Some case studies help us understand how advances in understanding artificial consciousness can contribute to creating ethical AI systems.